Artifact reduction in the CSPAD detectors used for LCLS experiments. (22nd August 2017) - Pietrini, Alberto; Nettelblad, Carl
Abstract : An under‐diagnosed detector artifact is reported and corrected for in a sparse photon‐counting regime. Standard deviation in false‐positive photon count is reduced by up to 35%, with improved or identical true positive rates. Abstract : The existence of noise and column‐wise artifacts in the CSPAD‐140K detector and in a module of the CSPAD‐2.3M large camera, respectively, is reported for the L730 and L867 experiments performed at the CXI Instrument at the Linac Coherent Light Source (LCLS), in low‐flux and low signal‐to‐noise ratio regime. Possible remedies are discussed and an additional step in the preprocessing of data is introduced, which consists of performing a median subtraction along the columns of the detector modules. Thus, we reduce the overall variation in the photon count distribution, lowering the mean false‐positive photon detection rate by about 4% (from 5.57 × 10 −5 to 5.32 × 10 −5  photon counts pixel −1 frame −1 in L867, cxi86715) and 7% (from 1.70 × 10 ‐3 to 1.58 × 10 −3  photon counts pixel −1 frame −1 in L730, cxi73013), and the standard deviation in false‐positive photon count per shot by 15% and 35%, while not making our average photon detection threshold more stringent. Such improvements in detector noise reduction and artifact removal constitute a step forward in the development of flash X‐ray imaging techniques for high‐resolution, low‐signal and in serial nano‐crystallography experiments at X‐ray free‐electron laser facilities.